Designing knowledge-driven digitalization: novel recommendations for digitally supported multi-professional collaboration - Meindl, Oliver; Peuten, Sarah; Striebel, Xena; Gimpel, Henner; Ostgathe, Christoph; Schneider, Werner; Steigleder, Tobias (Frontiers in Digital Health, 2025)
IntroductionPalliative care is based on the principle of multi-professional collaboration, which integrates diverse competencies and perspectives to provide holistic care and support for patients and their relatives. In palliative care teams, there is an intensive exchange of information and knowledge; however, current documentation and hospital information systems often fall short of meeting the specific demands for effective collaboration and dynamic communication in this field.MethodsThis action design research study is based on the three-and-a-half-year interdisciplinary research project PALLADiUM and aims to demonstrate the added value of knowledge-driven digitalization.Results and discussionOur study provides novel recommendations for digitally supported multi-professional collaboration tailored to the specific requirements of palliative care and similar fields. Based on the analytical distinction between ‘information’ and ‘knowledge,’ we present design recommendations for co-creative, knowledge-driven development processes and multi-professional collaboration support systems. We further illustrate how these recommendations have been implemented into a functional technical demonstrator and outline how our results could impact future digitalization initiatives in healthcare.